1996
DOI: 10.1128/jb.178.6.1607-1613.1996
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional osmotic regulation of the sigma(s) subunit of RNA polymerase in Escherichia coli

Abstract: The s subunit of RNA polymerase (encoded by the rpoS gene) is a master regulator in a complex regulatory network that governs the expression of many stationary-phase-induced and osmotically regulated genes in Escherichia coli. rpoS expression is itself osmotically regulated by a mechanism that operates at the posttranscriptional level. Cells growing at high osmolarity already exhibit increased levels of s during the exponential phase of growth. Osmotic induction of rpoS can be triggered by addition of NaCl or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
164
1
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 36 publications
6
164
1
5
Order By: Relevance
“…leuO is located at 1.83 min of the current physical map of the E. coli chromosome (Berlyn et al, 1996), and the location of Tn10-8 at this position was confirmed by P1 (D, E and F). The fusions used were the transcriptional r poS742 ::lacZ fusion (A and D) and the translational r poS742 ::lacZ (B and E) and r poS379 ::lacZ (C and F) fusions (Lange and Hengge-Aronis, 1994;Muffler et al, 1996a). Optical densities (circles) and specific ␤-galactosidase activities (triangles) were determined throughout the growth cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…leuO is located at 1.83 min of the current physical map of the E. coli chromosome (Berlyn et al, 1996), and the location of Tn10-8 at this position was confirmed by P1 (D, E and F). The fusions used were the transcriptional r poS742 ::lacZ fusion (A and D) and the translational r poS742 ::lacZ (B and E) and r poS379 ::lacZ (C and F) fusions (Lange and Hengge-Aronis, 1994;Muffler et al, 1996a). Optical densities (circles) and specific ␤-galactosidase activities (triangles) were determined throughout the growth cycle.…”
Section: Resultsmentioning
confidence: 99%
“…by the addition of NaCl or sucrose (Muffler et al, 1996a), temperature downshift (Sledjeski et al, 1996) and during late exponential phase above a certain cell density, when cells are grown in minimal medium (Lange and Hengge-Aronis, 1994). S proteolysis is more or less strongly inhibited in response to starvation (Lange and Hengge-Aronis, 1994;Takayanagi et al, 1994), high osmolarity (Muffler et al, 1996a), heat shock (Muffler et al, 1997a) and, probably, shift to acid pH (Bearson et al, 1996). So far, osmotic upshift is the only known stress condition that at the same time stimulates rpoS translation and almost completely inhibits S degradation (Muffler et al, 1996a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RpoS는 세균 증식이 가장 활발한 대수기에서 높은 농도의 삼 투압 (Muffler et al, 1996b), 산성 pH (Bearson et al, 1996), 낮 은 온도의 생장조건과 (Sledjeski et al, 1996) 열 충격 (Muffler et al, 1997), 낮은 마그네슘 농도 (Tu et al, 2006), 산화적 스트레 스 (Loewen and Hengge-Aronis, 1994 (Gottesman, 2004). 합성된 RpoS 단백질은 정상적인 생장조건이 주어진 경우 대수기에서 많은 양이 지속적으로 생성되지만 외부 스트레스가 없는 경우 불안정하여 반감기가 3분 이내로 빠르게 분해되어 단백질 농도 가 크게 감소한다 (Lange and Hengge-Aronis, 1994;Loewen and Hengge-Aronis, 1994;Moreno et al, 2000).…”
Section: Rpos의 발현unclassified
“…세균이 빠르게 성장할 수 있는 조건에서도 RpoS 합성이 이루어지지만, 합성되는 즉시 RssB에 의해 ClpXP에 전달 되어 분해된다 (Muffler et al, 1996b;Pratt and Silhavy, 1996 (Jenal and Hengge-Aronis, 2003). RpoS는 ClpP에 의해 분해되 는데, ClpP는 serine-type protease로서 ClpA나 ClpX와 복합체 를 구성하여 단백질을 분해시킨다 (Li et al, 2010).…”
Section: Rpos의 발현unclassified